Health and Beauty : A Book for Girls - Foley, Elizabeth; Cocker, Edith A. (London : The Health & Cleanliness Council)
1939-10 1939 1930s 27 pages ; illustrations First edition 1928 Reprinted January 1929 Reprinted March 1929 Reprinted June 1929 Second edition Sept. 1929 Reprinted November 1929 Reprinted January 1930 Reprinted May 1930 Reprinted October 1930 Reprinted January 1931 Reprinted December 1932 Reprinted August 1933 Reprinted October 1933 Reprinted January 1934 Revised May 1934 Reprinted July 1934 Reprinted October 1934 Reprinted January 1935 Reprinted June 1935 Reprinted October 1935 Reprinted January 1936 Reprinted April 1936 Reprinted June 1936 Reprinted October 1936 Reprinted April 1937 Reprinted September 1937 Reprinted November 1937 Revised March 1938 Reprinted October 1938 Revised January 1939 Reprinted October 1939 177/5/8/4